Optimal biomaterials for tracheal epithelial grafts: An in vitro systematic comparative analysis. (November 2018) - Varma, Ratna; Aoki, Fabio G.; Soon, Kayla; Karoubi, Golnaz; Waddell, Thomas K.
Graphical abstract: Abstract: Tracheal injury, stenosis, and malignancy demand tracheal reconstruction, which often fails due to the lack of a functioning epithelium. We performed an extensive comparative analysis to determine optimal biomaterials for developing tracheal epithelial grafts with mucociliary function. We screened Hyaluronan-Poly(Ethylene Glycol), Chitosan-Collagen, Collagen Vitrigel Membrane, Fibrin Glue, Silk Fibroin, and Gelatin based on various parameters including mechanical strength, bulk degradation, cell attachment, spreading, metabolic activity, focal adhesion formation, and differentiation into ciliated and goblet cells. Silk Fibroin had significantly higher tensile strength (21.23 ± 4.42 MPa), retained 50% of its mass across 5 weeks, allowed 80–100% cell spreading and increasing metabolic activity across 10 days, focal adhesion formation within 2 h, and differentiation into 5.9 ± 2.6% goblet cells. Silk Fibroin, however, led to poor ciliation, producing 5.5 ± 3.9% ciliated cells, whereas Collagen Vitrigel Membrane promoted excellent ciliation. To capitalize on the mechanical and differentiation benefits of its respective components, we developed a composite biomaterial of Silk Fibroin and Collagen Vitrigel Membrane (SF-CVM), which demonstrated enhanced maturation into 20.6 ± 1.7% ciliated and 5.6 ± 1.0% goblet cells. Development of biomaterials-based airway epithelial grafts that provide desirable mechanics and differentiation is a major step towards treatment of airway disease. Statement of Significance: Tracheal blockage, injury, and malignancy greater than 50% of the adult tracheal length cannot be safely resected. Tracheal replacement is one approach, but a major cause of transplant failure is the lack of a functioning epithelium. While tissue engineering for tracheal regeneration using biomaterials is promising, there is currently no gold standard. Therefore, we performed a systematic comparative study to characterize relevant materials for generating a biomaterials-based airway epithelial graft. We developed a composite biomaterial intended for surgical implantation providing tensile strength, slow biodegradation, and optimal support for differentiation of mature epithelia. This is a significant step augmenting current state-of-the-art methods for airway surgeries, laryngeal reconstruction, and tracheal tissue engineering.